Transnational Work Migration of Nepali Youths: The Changing Phenomena and the Context of Achieving Education - Adhikari, Dhruba Singh (Journal of Education and Research, 2019)
This literature-based paper has concentrated on the transnational work migration of Nepali youths. The high poverty, minimum opportunities and shifting nature of the profession of the country and desired options, income differences and feeling of the secured mentality of the migrants have been analysed through the perspective of push and pull model and its continuity through the lens of network theory. Concurrently, the remittances have become a prominent resource for the country and its total share of gross domestic product (GDP) has reached more than 29 per cent. Increasing remittance itself clarifies that the out-migration of Nepali youths is towering and consistent. Escalating abroad migration for work has become a contemporary issue and buzzword. At the same time, foreign employment is amplifying the educational gap. Accordingly, government initiation towards the sector has centralised highly even though it is not sufficient. The fear of ‘brawn drain’ as well as 'brain drain' is broadening and deepening in a rapid pace in general, and the adverse impact of it in the country to some extent is reverberating in particular. Nevertheless, comparatively less work has been done to utilise the achieved skills of the migrated youths.